Low dopamine transporter binding in the nucleus accumbens in geriatric patients with severe depression. Issue 8 (26th May 2020) - Moriya, Hiroki; Tiger, Mikael; Tateno, Amane; Sakayori, Takeshi; Masuoka, Takahiro; Kim, WooChan; Arakawa, Ryosuke; Okubo, Yoshiro
Abstract : Aim: Dysfunction of dopaminergic neurons in the central nervous system is considered to be related to major depressive disorder (MDD). Especially, MDD in geriatric patients is characterized by anhedonia, which is assumed to be associated with reduced dopamine neurotransmission in the reward system. Dopamine transporter (DAT) is considered to reflect the function of the dopamine nerve system. However, previous DAT imaging studies using single photon emission computed tomography or positron emission tomography (PET) have shown inconsistent results. The radioligand [ 18 F]FE‐PE2I for PET enables more precise evaluation of DAT availability. Hence, we aimed to evaluate the DAT availability in geriatric patients with MDD using [ 18 F]FE‐PE2I. Methods: Eleven geriatric patients with severe MDD and 27 healthy controls underwent PET with [ 18 F]FE‐PE2I, which has high affinity and selectivity for DAT. Binding potentials ( BP ND ) in the striatum (caudate and putamen), nucleus accumbens (NAc), and substantia nigra were calculated. BP ND values were compared between MDD patients and healthy controls. Results: MDD patients showed significantly lower DAT BP ND in the NAc ( P = 0.009), and there was a trend of lower BP ND in the putamen ( P = 0.032) compared to controls. Conclusion: We found low DAT in the NAc and putamen in geriatric patients with severe MDD, which could be related to dysregulation of the reward system.